Syntactic Analysis of Legal Criticism in Karni Ilyas’ Articles - Nai Supartini; John Pahamzah (Journal of English Language Teaching and Cultural Studies, 2023)
The study investigated the syntactic analysis of the Legal Criticism Articles in Catatan Hukum II written by Karni Ilyas to know the explicit and implicit message in the article. The method used in the research is qualitative by analysing the article based on syntactic analysis. The result shows that the transitive active sentences appear most frequently that are marked by linguistic markers of objects and complements in each of the active sentences. There are also some transitive active sentences, semi-transitive active sentences, and intransitive active voices found in the active sentences of the article. Conditional passive sentences also appear most frequently followed by action passive sentences, intransitive passive sentences, and transitive passive sentences. It can be concluded that Karni Ilyas, apart from wanting to state that the government as a subject who takes action also always sees problems as the government's responsibility. This can be seen from the active sentences used in the article. In addition, Karni Ilyas always places the people or society as subjects or as victims in passive sentences when analysed from the passive sentences used in articles.